Determination of molybdenum in high-purity iron by radiochemical neutron activation analysis - SUZUKI, Shogo; YAMAGUCHI, Naoki; HIRAI, Shoji; OKADA, Yukiko; MITSUGASHIRA, Toshiaki (BUNSEKI KAGAKU, 1999)
A new radiochemical procedure was developed for the isolation of activated molybdenum in high-purity iron irradiated by thermal neutrons. After irradiation, the sample was first dissolved in hydrochloric acid, and then (NH4)3PO4·12MoO3·3H2O(PMA) powder was added into the solution. To remove a major amount of the iron, ferric hydroxide were precipitated by the addition of NH4OH, while activated molybdenum remained in the alkaline solution as PMA. In order to attain high decontamination of up to 105 of iron from PMA, a trace amount of the remaining iron was removed by cation-exchange chromatography, and PMA was precipitated by adding excess hydrochloric acid. Finally, the precipitates were mounted for a sample for gamma-ray spectrometry. The overall recovery of activated molybdenum was 84%. The procedure was successfully applied to the determination of a ppb amount of molybdenum in high-purity iron.